Characterisation of large area THGEMs and experimental measurement of the Townsend coefficients for CF4. (19th October 2017) - Burns, J.; Crane, T.; Ezeribe, A.C.; Grove, C.L.; Lynch, W.; Scarff, A.; Spooner, N.J.C.; Steer, C.
Abstract: Whilst the performance of small THGEMs is well known, here we consider the challenges in scaling these up to large area charge readouts. We first verify the expected gain of larger THGEMs by reporting experimental Townsend coefficients for a 10 cm diameter THGEM in low-pressure CF_4 4 . Large area 50 cm by 50 cm THGEMs were sourced from a commercial PCB supplier and geometrical imperfections were observed which we quantified using an optical camera setup. The large area THGEMs were experimentally characterised at Boulby Underground Laboratory through a series of gain calibrations and alpha spectrum measurements. ANSYS, Magboltz and Garfield++ simulations of the design of a TPC based on the large area THGEMs are presented. We also consider their implications for directional dark matter research and potential applications within nuclear security.